Parameter Analisis Penelitian Interaksi Sosial Pada Ruang Publik Di Kompleks Perumahan Formal: Parameter Interaksi Sosial di Ruang Publik Perumahan - Siregar, Fernando Septony (Ide dan Dialog Desain Indonesia (Idealog), 2024)
Formal housing stands out as the most favored residential environment for individuals of all ages. Beyond its appealing architectural design, formal housing places a premium on safety, security, and access to public space amenities. These amenities are envisioned to serve as forums for positive social engagement, fostering a sense of belonging, camaraderie, and cohesion. Studies have shown that social interaction in public spaces correlates with heightened place attachment and improved social well-being among residents. This research endeavors to devise an assessment methodology capable of gauging the quality of social interaction in residential public spaces. The ultimate goal is to develop several assessment frameworks derived from a comprehensive literature review on social interaction quality within formal housing complexes. These frameworks will identify key aspects such as social interaction participants, temporal dynamics, activity types, intensity levels, and behavioral settings.